DESAIN TAMAN IN-DOOR HYDROPONIC UNTUK BANGUNAN PUBLIK BERLAHAN SEMPIT DI SURAKARTA - Prasetyo, Ersnathan Budi; Purnomo, Agung (Institut Seni Indoensia Surakarta, 2020)
Abstract Parks are important parts that cannot be left out in the design of urban landscape, architecture and interior design. Its existence is able to provide a fresh and comfortable atmosphere so that the quality of human life will be better. In its development, the availability of an ideal park in an urban environment is felt to be lack due to the increasingly limited land such as the narrow yard of the house or even no more area to make the park. Another challenge is how to utilize limited areas for in-door parks in both residential and public buildings that are more practical and efficient. This applied research aims to address this problem by offering a garden design with a hydroponic planting system which is now commonly used in agriculture or plantations to be applied to in-door garden designs. The research carried out in Surakarta is the process through identification, design experiments and design trials. The data in the form of artifacts, literature, and informants is carried out through observation, study of literature, interviews, and documentation. Design experiments are carried out using a design and aesthetic approach strengthened by an evocative, educative, psychological and socio-cultural approach. The SWOT analysis model is used in designing in-door garden designs. Design trials is executed through the activities of realizing design (experimental products) and their application (design implementation), evaluation, refinement of design concepts and formulation of recommendations. Keywords: in-door garden, hydroponic, narrow land, Surakarta. Abstrak Taman merupakan bagian penting yang tidak bisa ditinggalkan dalam perancangan landskap kota, arsitektur dan desain interior. Keberadaannya mampu memberikan suasana segar dan nyaman sehingga kaulitas hidup manusia akan menjadi lebih baik. Dalam perkembanganya tersedianya taman yang ideal di lingkungan perkotaan dirasakan masih kurang oleh karena semakin terbatasnya lahan seperti sempitnya halaman rumah atau bahkan tidak ada lagi area untuk dibuat taman. Hal lainnya adalah bagaimana memanfaatkan area-area yang terbatas untuk taman in-door baik di rumah tinggal maupun bangunan umum yang lebih praktis dan efisien juga menjadi sebuah tantangan. Penelitian terapan ini bertujuan menjawab permasalahan tesebut dengan menawarkan sebuah desain taman dengan sistem tanam hydroponic yang pada masa sekarang biasa digunakan dalam pertanian atau perkebunan untuk diaplikasikan ke dalam desain taman in-door. Penelitian yang dilakukan di Surakarta ini prosesnya melalui identifikasi, eksperimen desain dan uji-coba desain. Untuk menggali data yang berupa artefak, literatur, dan informan dilakukan melalui observasi, studi literatur, wawancara, dan dokumentasi. Eksperimen desain dilakukan dengan pendekatan desain dan estetis diperkuat oleh pendekatan evokatif, edukatif, psikologi dan sosio-budaya. Model analisis SWOT dipakai ketika akan melakukan perumusan desain taman in-door. Uji-coba desain melalui kegiatan mewujudkan desain (produk eksperimen) dan penerapannya (implementasi desain), evaluasi, penyempurnaan konsep desain dan perumusan rekomendasi. Keywords: taman in-door, hydroponic, lahan sempit, Surakarta.